Perception and Practices of Personal Financial Management among Generation Z in Indonesia - Ahmad Fathoni Ardyansyah; Nur Khusniyah Indrawati (Journal Research of Social Science, Economics, and Management, 2024)
Generation Z, born between 1995 and 2010, is notable for its proficiency with technology, social media presence, expressiveness, tolerance, and multitasking abilities. The advancement of technology, combined with these qualities, raises the possibility that Generation Z will have consumerist tendencies. This study aims to examine Generation Z's perceptions and practices of personal financial management in Indonesia. The research employs a qualitative approach with data collection through literature review. The Significance of Personal Financial Management, Building Economic Stability Through Financial Literacy are some of the major subjects that were investigated. The results revealed that by managing their finances, Generation Z may achieve their goals, protect themselves from uncertainty, and contribute significantly to society. Personal financial management is essential for ensuring financial security and personal well-being. Developing financial literacy in Generation Z is obviously vital to ensuring economic stability. Providing people with the knowledge and abilities to handle their money wisely helps to improve both their financial security and the overall stability of the economy. One of the primary responsibilities of the Indonesia Financial Services Authority, also known as Otoritas Jasa Keuangan, or OJK, is to promote financial literacy throughout the country. Financial literacy is critical for both individual financial well-being and economic stability.